Pemberdayaan Kelompok Suami Desa Lagaruda Kecamatan Sanrobone Kabupaten Takalar Sebagai Upaya Pencegahan Kematian Ibu Melalui Inovasi Program Tetta Siaga (TESI) - Yusriani, Yusriani; Alwi, Muhammad Khidri; Asrina, Andi (JOURNAL OF TRAINING AND COMMUNITY SERVICE ADPERTISI (JTCSA), 2022)
Lagaruda Village, Sanrobone District, Takalar Regency is one area that has cases of maternal and child mortality. One of the indirect causes of maternal death is the lack of the husband's role in preventing maternal mortality. So far, counseling or training is only given to pregnant women. Therefore, it is necessary to have special class activities for husbands that are packaged in the innovation of the Tetta Siaga Program (TESI). The specific goals and targets to be achieved are to increase the knowledge and skills of the husband's group regarding pregnancy care, delivery assistance, the postpartum period and newborn care, Family Planning and Parenting Programs, use and distribution of equipment and facilities needed by the wife during pregnancy, childbirth. , postpartum, and child care. Efforts to take care of children are a joint task of the wife, so that the husband's stigma about the various risks faced by the wife can be further increased to carry out various prevention efforts. The method that will be used in achieving this goal is a participatory approach with brainstorming, demonstration, discussion methods and training/practice methods to increase knowledge and train husband's group skills. To observe and evaluate the knowledge and abilities of the husbands' groups using a pre-post test questionnaire, and a skill checklist both before, during the process and after education and training on the Tetta Siaga Innovation Program.